Attentional Biases toward Face-Related Stimuli among Face Dissatisfied Women: Orienting and Maintenance of Attention Revealed by Eye-Movement - Kou, Hui; Su, Yanhua; Bi, Taiyong; Gao, Xiao; Chen, Hong (Frontiers in Psychology, 2016)
The present study was aimed to examine attentional biases towards attractive and unattractive faces among face dissatisfied women. 27 women with high face dissatisfaction (HFD) and 27 women with low face dissatisfaction (LFD) completed a visual dot-probe task while their eye-movements were tracking. Under the condition of faces-neutral stimuli (vases) pairs, compared to LFD women, HFD women directed their first fixations more often towards faces, directed their first fixations towards unattractive faces more quickly, and had longer first fixation duration on such faces. All participants had longer overall gaze duration on attractive faces than on unattractive ones. Our behavioral data revealed that HFD women had difficulty in disengaging their attention from faces. However, there are no group differences in stimulus pairs containing an attractive and an unattractive face. In sum, when faces were paired with neutral stimuli (vases) HFD women showed an attention pattern characterized by orienting and maintenance, at least initially, towards unattractive faces but showed overall attention maintenance to attractive ones, but any attention bias wasn’t found in attractive - unattractive face pairs.